1998
DOI: 10.1111/j.1469-7793.1998.603be.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurements of the triceps surae complex architecture in man: implications for muscle function

Abstract: The objectives of this study were to (1) quantify experimentally in vivo changes in pennation angle, fibre length and muscle thickness in the triceps surae complex in man in response to changes in ankle position and isometric plantarflexion moment and (2) compare changes in the above muscle architectural characteristics occurring in the transition from rest to a given isometric plantarflexion intensity with the estimations of a planimetric muscle model assuming constant thickness and straight muscle fibres. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
409
21
12

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(495 citation statements)
references
References 22 publications
53
409
21
12
Order By: Relevance
“…The reliability of our ultrasound measurements has previously been reported (Manal et al, 2006) and compares favorably with values reported in the literature (Fukunaga et al, 1997;Maganaris et al, 1998). The coefficient of variation for scanning a site multiple times and computing the pennation angle for each scan was 8.5%.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The reliability of our ultrasound measurements has previously been reported (Manal et al, 2006) and compares favorably with values reported in the literature (Fukunaga et al, 1997;Maganaris et al, 1998). The coefficient of variation for scanning a site multiple times and computing the pennation angle for each scan was 8.5%.…”
Section: Resultssupporting
confidence: 71%
“…Results from recent studies using real-time ultrasonography question these inherent assumptions of the planimetric model (Hodges et al, 2003, Maganaris et al, 1998, Muramatsu et al, 2002. For example, Maganaris and colleagues (1998) showed that a planimetric model underestimated pennation angle at MVC by 12° and 14° for the lateral gastrocnemius and soleus compared to in vivo measures recorded using ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The architectural properties of small numbers of human lower extremity muscles have been reported in several studies, some of which used indirect methods to assess the architecture [11,14,23,26]. The two most extensively used data sets representing direct measurements of human lower extremity architecture consist of only five specimens of unknown size, gender, and age [8,30].…”
Section: Introductionmentioning
confidence: 99%